Policy-oriented, school-based physical activity intervention to prevent childhood obesity in China (the health legacy project of the second Summer Youth Olympic Games): a cluster randomised trial. (November 2016) - Xu, Fei; Wang, Zhiyong; Ye, Qing; Tse, Lap Ah; Xue, Hong; Tan, Zhengqi; Wang, Youfa
Abstract: Background: School-based physical activity intervention programmes are potentially effective in prevention of childhood obesity, but evidence was primarily from small-scale intervention trials (n<1000). On the basis of suggestions from International Olympic Committee and policy support from the local government, we extended knowledge and strategies from our previous similar trial on physical activity promotion (n=1108) to a large-scale, policy-oriented, school-based physical activity intervention programme, the Health Legacy Project of the second Summer Youth Olympic Games, which aimed to prevent childhood obesity in the general student population. We aimed to test the feasibility and effectiveness of this intervention in Nanjing, China, the host city of the Youth Olympic Games in 2014. Methods: In this cluster randomised trial, we randomly selected fourth graders and seventh graders from 32 primary schools and 16 junior high schools from eight districts in Nanjing. Students were randomly assigned (1:1) into either intervention or control groups at the school level. Routine health education was provided to all schools, while the intervention schools additionally received a tailored 1 year multicomponent physical activity intervention programme that was integrated into the regular curriculum. Interventions included classroom curriculum and the corresponding blackboard show (ie, a themed presentation board in each classroom), school environment support, family involvement, and fun programmes and events. The 1-year primary outcome was physical activity levels (ie, time of moderate-intensity physical activity [metabolic equivalent 3–6] plus double the time of vigorous-intensity physical activity [≥6]), assessed with a validated questionnaire. Bodyweight and height were objectively measured. We used difference-in-difference models to examine the intervention's effects on physical activity levels and weight at the individual level by treatment group. We used mixed-effect models to adjust for clustering. Ethics approval was granted by the Academic and Ethical Committee of Nanjing Municipal Center for Disease Control and Prevention, and all participants provided written informed consent. Findings: Of 10 901 students enrolled (mean age 9·0 years [SD 0·4] for fourth graders and 12·0 years [0·4] for seventh graders), 9858 (97·7%) completed the follow-up survey. No significant differences in terms of age, sex, BMI, and parental education were noted between the control and intervention groups at baseline or between those who completed the follow-up survey at study end and those who did not. Compared with baseline, physical activity level increased by a mean of 33·13 min (SD 788·50) per week in the intervention group but decreased by 1·76 min (7880·20) per week in the control group (p=0·028). After adjustment for participants' age, sex, baseline body weight, red meat consumption at baseline (adjusted for assessing BMI and its z score), and parents' educational level, students in the intervention group were more likely to have increased time of moderate physical activity than those in the control group (odds ratio [OR] 1·15, 95% CI 1·06–1·25). Compared with the control group, the intervention group had a smaller increase in mean BMI (0·22 [SD 1·23] vs 0·46 [1·67]; β −0·3, 95% CI −0·5 to −0·1) and BMI z score (0·07 [0·40] vs 0·16 [0·53]; β −0·1, 95% CI −0·2 to −0·03). Fewer students in the intervention group were obese (adjusted OR 0·7, 95% CI 0·6–0·9) or overweight or obese (adjusted OR 0·8, 0·7–1·0) at study end. The intervention group had fewer new events of excess bodyweight (269 [8%] of 3429 vs 277 [9%] of 3017; p=0·054) and a larger proportion of formerly overweight or obese students having normal bodyweight by study end (221 [12%] of 1845 vs 143 [9%] of 1567]; p=0·008). Interpretation: This policy-oriented, multicomponent, school-based physical activity programme was scalable and effective in increasing physical activity and preventing obesity in Chinese children. The intervention strategies can be readily translated into large-scale obesity prevention programmes in a range of schools in China. Funding: Nanjing Medical Science and Technique Foundation (ZDX12019), China.